Morphological responses of six sorghum varieties on cadmium-contaminated soil - NUR AZIZAH USWATUN HASANAH; EDI PURWANTO; PUJI HARSONO; SAMANHUDI SAMANHUDI; AMALIA TETRANI SAKYA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Hasanah NAU, Purwanto E, Harsono P, Samanhudi, Sakya AT. 2023. Morphological responses of six sorghum varieties on cadmium-contaminated soil. Biodiversitas 24: 3903-3915. Six sorghum varieties were planted on cadmium-contaminated soil and characterized from April to July 2020 at a rice field in Balecatur Gamping, Yogyakarta. The objectives of this experiment were to characterize themorphological responses of six sorghum varieties and select a variety with a high biomass and Cd uptake fora potential phytoremediator. This experiment used six sorghum varieties, namely Super-1, Samurai-1, Suri-3, Numbu, Kawali, and Hitam, following completely randomized design procedures with four replications. The observation of morphological and agronomical characteristics focused on ten plants as the sample of each plot. The result showed that there were differences in the morphological and agronomical characteristics among six sorghum varieties. Varieties were assessed in terms of distinctness and grouped based on the time of panicle emergence, plant height, panicle shape, and caryopsis color. There were threeclasses as follows: Class 1, i.e., time of panicle emergence: very early (Super-1, Suri-3, Numbu, and Hitam); plant height: long (Super-1), medium (Suri-3), short (Numbu and Hitam); panicle shape: panicle broader in the upper part (Numbu), symmetrical (Super-1 and Suri-3), pyramidal (Hitam); caryopsis color: white (Super-1), grayish orange (Suri-3 and Hitam), yellowish orange (Numbu). Class 2, time of panicle emergence: early (Samurai-1); plant height: medium (Samurai-1); panicle shape: panicle broader in the lower part (Samurai-1); caryopsis color: yellowish orange (Samurai-1). Class 3, time of panicle emergence: medium (Kawali); plant height: medium (Kawali); panicle shape: panicle broader in the lower part (Kawali); caryopsis color: yellowish white (Kawali). Assessment of agronomical characteristics revealed that fresh plant weight had a significant positive correlation with plant height R1, plant height R5, stem diameter, leaf bladewidth, thousand-grain weight, and stem sugar content. Several varieties, namely Super-1, Samurai-1 and Kawali, were found to have excellent agronomical characteristics to provide a solid varietal basis for selecting varieties as phytoremediators.